Stairway to health: an analysis for workplace stairs design and use - McGann, S.; Creagh, Robyn; Tye, Marian; Jancey, Jonine; Pages-Oliver, R.; James, Hami (2015)
This paper reflects on a recent workplace design and physical activity study to argue for a radical rethinking of staircase design in office buildings. This paper deploys design analysis of three campus buildings alongside objective physical activity data and survey responses of study participants in these buildings (n=111) to identify limitations to past and current staircase design approaches. Working within a social ecological framework, this paper builds on observations of higher education office-based worker’s physical activity, attitudes to movement at work, and building design. The different approaches to staircase design from each of the three buildings from three different decades (1970s, 1980s, 1990s) within the study demonstrate shifts in architectural attitude to circulation design. Two key findings emerge. Firstly, that current health-focused design guides or staircase design audits do not go far enough in identifying the social-ecological environment which supports stair use. Secondly, that a radical rethinking during the design process of staircase design in office buildings may be needed to support at-work physical activity. This paper is significant in centring architectural design practice as a way of understanding physical activity behaviours within workplaces and finding ways of extending contemporary responses to population health dilemmas.